Institutional Economic Theory: the Scientific and Theoretical Preconditions of Origin (German Historical School) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with the scientific achievements of the scholars of the German historical school of classical political economy, which positively influenced the further development of economic science and, in particular, the institutional economic theory.On the basis of studying the works of scientists it was established that the borrowing by the founders of the named theory of the necessity of considering economic, legal and social relations in unity, addressing the problems of morality, culture, the spirit of society, use, in the analysis of economic life, the state of development of socio-cultural environment, deepened the process of studying noneconomic factors of economic activity.The use of systematic in the study of the economy increased the number of tools in the process of scientific research, contributed to the dissemination of historical method of research, as well as the introduction of an interdisciplinary approach.
Keywords: economic theory, economic thought, institutional economic theory, German historical school, direction of economic thought, historical method of research